Put your money where your life is : how to invest locally through self-directed IRAs and solo 401ks - Shuman, Michael (Berrett-Koehler Publishers, 2020)
"Local investing guru Michael Shuman shows how to use two neglected investment tools to invest in Main Street, not Wall Street, and get a good return too!"--